Thermally induced reorientation and plastic deformation of B19' monoclinic martensite in nanocrystalline NiTi wires. (1st January 2023) - Iaparova, E.; Heller, L.; Tyc, O.; Sittner, P.
Abstract: Functional behavior of nanocrystalline NiTi shape memory wires having various austenitic microstructures was investigated by thermomechanical testing and TEM analysis of martensite microstructures in deformed wires. Three phenomena are reported and discussed in this work. First, it is observed that martensitic NiTi wire heated under low applied stresses elongates several percent before it shortens due to reverse martensitic transformation. This phenomenon is explained as being due to thermally induced martensite reorientation proceeding via motion of interfaces between (001) compound twin domains existing in the microstructure of selfaccommodated B19' martensite. Second, it is shown that martensite stabilization by deformation (upward shift of the As temperature after deformation in martensite) is not caused by plastic deformation and lattice defects introduced by deformation, as frequently argued in the literature, but that it is due to change of martensite variant microstructures in polycrystal grains during the reorientation process. Finally, it is observed that generation of unrecovered plastic strains and dislocation defects accompanies all martensitic transformation/reorientation/detwinning/ processes in NiTi, though in different extents. It is found that: i) no plastic strains and lattice defects are generated by martensitic transformation proceeding in the absence of external stress, ii) plastic strains, which are generated by martensitic transformations proceeding under external stress, are significantly larger than plastic strains generated during reorientation or detwinning processes in martensite, iii) plastic strains generated while the wire shortens during reverse transformation upon heating are larger than plastic strains generated while it elongates upon forward transformation on cooling. It is proposed that plastic deformation proceeds in the oriented martensite phase via [100](001) dislocation slip. The coupled martensitic transformation and [100](001) dislocation slip in martensite constitutes a TWIP/TRIP like deformation mechanism enabling functional fatigue of NiTi taking place at low stresses below the yield stress for plastic deformation of martensite. Graphical abstract: Image, graphical abstract